(untitled) (Bangladesh Pharmaceutical Journal, 2025)
Mentha viridis has been used as folk medicine traditionally for diverse pharmacological activity and used worldwide for its aroma for different purposes in particular with tea. This research was investigated to examine the antioxidant and antibacterial activities of ethanolic extract of M. viridis. The antioxidant capacity was assessed by several assays namely DPPH free radical scavenging assay, total antioxidant assay, total phenolics and total flavonoids content assay. Determination of total phenolics and total flavonoids were performed spectrophotometrically using Folin-Ciocalteu reagent and aluminium chloride colorimetric assay methods respectively, while the free radical scavenging activity was estimated by DPPH (2, 2-diphenyl-2-picrylhydrazyl) method. The antibacterial activity was estimated by agar disk diffusion method against a number of bacterial strains. The results exhibited that ethanolic extract M. viridis is the abundant source of phenolics and flavonoids but the total antioxidant activity was detected to be the highest in comparison to other phytochemical constituents. Extract showed robust free radical scavenging activity at a concentration of 500 μg/ml. The ethanolic extract of M. viridis displayed moderate inhibitory activity against the microorganisms S. aureus and E.coli. The interpretation stipulates that ethanolic extract of M. viridis is a potential origin of natural antioxidants due to presence of mainly polyphenolic components in it. Bangladesh Pharmaceutical Journal 28(1): 1-10, 2025 (January)